Transcriptional time course after rotator cuff repair in 6 month old female rabbits - Vasquez-Bolanos, Laura S.; Gibbons, Michael C.; Ruoss, Severin; Wu, Isabella T.; Esparza, Mary C.; Fithian, Donald C.; Lane, John G.; Singh, Anshuman; Nasamran, Chanond A.; Fisch, Kathleen M.; Ward, Samuel R. (Frontiers in Physiology, 2023)
Rotator cuff tears are prevalent in the population above the age of 60. The disease progression leads to muscle atrophy, fibrosis, and fatty infiltration, which is not improved upon with surgical repair, highlighting the need to better understand the underlying biology impairing more favorable outcomes. In this study, we collected supraspinatus muscle tissue from 6 month old female rabbits who had undergone unilateral tenotomy for 8 weeks at 1, 2, 4, or 8 weeks post-repair (n=4/group). RNA sequencing and analyses were performed to identify a transcriptional timeline of rotator cuff muscle adaptations and related morphological sequelae. There were differentially expressed (DE) genes at 1 (819 up/210 down), 2 (776/120), and 4 (63/27) weeks post-repair, with none at 8 week post-repair. Of the time points with DE genes, there were 1092 unique DE genes and 442 shared genes, highlighting that there are changing processes in the muscle at each time point. Broadly, 1-week post-repair differentially expressed genes were significantly enriched in pathways of metabolism and energetic activity, binding, and regulation. Many were also significantly enriched at 2 weeks, with the addition of NIF/NF-kappaB signaling, transcription in response to hypoxia, and mRNA stability alongside many additional pathways. There was a also shift in transcriptional activity at 4 weeks post-repair- the DE genes were significantly enriched pathways of lipids, hormones, apoptosis, and cytokine activity despite an overall decrease in the number of differentially expressed genes. These transcriptional profiles were correlated with the histological findings of increased fat, degeneration, and fibrosis. At 8 weeks post-repair there were no DE genes when compared to control, possibly representing a steady state or general silencing of differential gene expression. Gene sets correlated with histological phenotypic traits and were enriched for fatty acid metabolism, TGF-B-related, and other pathways, but not for a positive anabolic response in the muscle to reloading. These results provide a platform for understanding and challenging the complex and diverse time course of biological processes in RC muscle after surgical repair.